Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/ja306726u
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical High-Surface-Area Carbons with Exceptional Hydrogen Storage Capacities: Open Carbon Frameworks

Abstract: A class of high-surface-area carbon hypothetical structures has been investigated that goes beyond the traditional model of parallel graphene sheets hosting layers of physisorbed hydrogen in slit-shaped pores of variable width. The investigation focuses on structures with locally planar units (unbounded or bounded fragments of graphene sheets), and variable ratios of in-plane to edge atoms. Adsorption of molecular hydrogen on these structures was studied by performing grand canonical Monte Carlo simulations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 52 publications
3
53
0
Order By: Relevance
“…Graphene, a two-dimensional (2D) structure of carbon atoms bonded in a hexagonal lattice, has attracted considerable attention within the scientific community for its outstanding properties, such as its electrical and thermal conductivity (1738 S m -1 and ~5·10 3 W m -1 K -1 respectively), [1][2][3][4] intrinsic carrier mobility (> 2·10 5 cm 2 V -1 s -1 ), [5,6] theoretical surface area (~2600 m 2 g -1 ), [7] mechanical strength (~118 GPa), and elastic modulus (~1 TPa). [8] The realization of a three-dimensional (3D) network of graphene sheets would significantly expand the usability of this remarkable material.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, a two-dimensional (2D) structure of carbon atoms bonded in a hexagonal lattice, has attracted considerable attention within the scientific community for its outstanding properties, such as its electrical and thermal conductivity (1738 S m -1 and ~5·10 3 W m -1 K -1 respectively), [1][2][3][4] intrinsic carrier mobility (> 2·10 5 cm 2 V -1 s -1 ), [5,6] theoretical surface area (~2600 m 2 g -1 ), [7] mechanical strength (~118 GPa), and elastic modulus (~1 TPa). [8] The realization of a three-dimensional (3D) network of graphene sheets would significantly expand the usability of this remarkable material.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, MOFs are built by the self-assembly of metal ions or clusters and polytopic bridging ligands under solvothermal conditions67. In contrast to inorganic porous materials such as zeolites or activated porous carbons, numerous choices of organic linkers together with many coordination geometries indicate that MOFs could be tailored by judicious combinations of the building blocks for specific applications6789. Theoretically, the incorporation of accessible nitrogen-donor groups, such as pyridine, imidazole, and tetrazole, into the pore walls of porous materials can dramatically affect the gas uptake capacity and selectivity of the materials, especially for CO 2 capture on account of the dipole-quadrupole interactions between the polarizable CO 2 molecule and the accessible nitrogen site10.…”
mentioning
confidence: 99%
“…Literature reports also indicated that the incorporation of accessible nitrogen-donor groups into the porous materials could enhance the CO 2 uptake capacity and selectivity111213141516. Such approach is strategically important for developing a low-carbon future by increasing the capacity of selective CO 2 capture and by enhancing the storage capacity of clean energy source, such as H 2 191112131415161718. However, competitive coordination of these Lewis basic nitrogen sites with metal ions or clusters is a great challenge in direct synthesis of MOFs1920.…”
mentioning
confidence: 99%
“…The pore width has been defined as the distance between the centers of the carbon atoms in the graphene sheet. The CH 4 -graphene interaction has been described by the standard analytical Steele potential [15][16][17][18]. This potential assumes that a CH 4 molecule interacts with carbon atoms in the graphene sheet through the Lennard-Jones (6-12) potential and renders the energy of the adsorbed particle as an integral over the whole graphene sheet.…”
Section: Pore Structuresmentioning
confidence: 99%
“…However, atomic corrugation of the graphitic wall is not explicitly treated in this paper as it represents a small fraction of the CH 4 -wall interaction energy. Its influence is negligible for the total storage capacity [15,18].…”
Section: Pore Structuresmentioning
confidence: 99%